The Urgency Development of Attractiveness in Bukit Khayangan Tourism Object Sungai Penuh City - Witro, Doli; Azmiya Putri, Luqyana; Adawiyah, Rabiyatul; Afrilia, Kesi; Alamin, Nurul (JURNAL DESTINASI PARIWISATA; Vol 8 No 1 (2020): VOL 8, NO 1 (2020): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2020)
In the era of globalization, the tourism sector is one of the largest and most influential industries in economic development in general. In the 21st century, the tourism sector will be the primary driver in the world economy. In tourism, there are elements contained in it, ranging from tourists, travel, tourist destinations, industry, and so forth. Tourism for foreign exchange sources, including Indonesia, which is one of the countries that have various types of tourism, namely natural tourism, social tourism, and cultural tourism spread from Sabang to Merauke. One of the regions in Indonesia where multiple types of natural wealth have the potential to be developed is Sungai Penuh City, located in the western area in the form of a plateau. The most popular highland tourist destination in Sungai Penuh City is Bukit Khayangan. Departing from the above, the author intends to develop these problems and raise them into an article that illustrates and discusses supporting factors and inhibiting factors in the development of the Bukit Khayangan attraction, Sungai Penuh City. Then the development of attractions in Bukit Khayangan, Sungai Penuh City city, as well as the contribution of Bukit Kayangan Kota Sungai Penuh attraction. Keywords: Object Development, Tourist Attraction, Bukit Khayangan